This bridge called my back : writings by radical women of color - Moraga, Cherríe; Anzaldúa, Gloria (SUNY Press, 2015)
"Through personal essays, criticism, interviews, testimonials, poetry, and visual art, this collection explores, as coeditor Cherrie Moraga writes, 'the complex confluence of identities--race, class, gender, sexuality--systemic to women of color oppression and liberation'"--Back cover.